Screen Media Exposure in Early Childhood and Its Relation to Children’s Self-Regulation - Berna A. Uzundağ; Merve Nur Altundal; Dilara Keşşafoğlu (Human Behavior and Emerging Technologies)
Self-regulation, the ability to control thoughts, emotions, and behavior for goal-directed activities, shows rapid development in infancy, toddlerhood, and preschool periods. Early self-regulatory skills predict later academic achievement and socioemotional adjustment. An increasing number of studies suggest that screen media use may have negative effects on children’s developing self-regulatory skills. In this systematic review, we summarized and integrated the findings of the studies investigating the relationship between young children’s screen media use and their self-regulation. We searched the ERIC, PsycINFO, PubMed, and Web of Science databases and identified 39 relevant articles with 45 studies. We found that screen time in infancy is negatively associated with self-regulation, but findings were more inconsistent for later ages suggesting that screen time does not adequately capture the extent of children’s screen media use. The findings further indicated that background TV is negatively related to children’s self-regulation, and watching fantastical content seems to have immediate negative effects on children’s self-regulatory skills. We suggest that future studies should take the content and context of children’s screen media use into account and also focus on parent- and home-related factors such as parental behaviors that foster the development of self-regulatory skills.